Dietary metal intake and the prevalence of erectile dysfunction in US men: Results from National Health and Nutrition Examination Survey 2001–2004 - Liu, Rui-Ji; Li, Shu-Ying; Xu, Zhi-Peng; Yu, Jun-Jie; Mao, Wei-Pu; Sun, Chao; Xu, Bin; Chen, Ming (Frontiers in Nutrition, 2022)
ABSTRACT Background: Erectile dysfunction (ED) mainly affects men over 40 years of age and is a common clinical condition. In addition to hypertension and diabetes, environment and lifestyle are also significantly associated with erectile dysfunction. The relationship between dietary trace metal intake and ED has not been studied. Methods: Data on participants were obtained from the National Health and Nutrition Examination Survey for this study, and those with incomplete information on clinical variables were excluded. Dose-response curve analysis was used to investigate the relationship between dietary trace metal intake and ED prevalence. Multivariate logistic regression analysis was used to adjust for confounders to further investigate the relationship between dietary trace metal intake and ED prevalence. 1:1 propensity score matching (PSM) was performed to adjust for differences between clinical variables for data reanalysis to confirm the reliability of the results. Results: A total of 3745 individuals were included in the study, including 1096 ED patients and 2649 participants without ED. Dietary intake of trace metals (Mg, Zn, Cu, Se) was significantly higher in participants without ED than in ED patients (all P<0.001). Dose-response curve analysis showed a significant negative association between these dietary metal intakes and ED prevalence (all P<0.001). Multivariate logistic regression analysis adjusted for confounders (age, education, BMI, annual household income, hypertension, diabetes, marital status, race, and current health status) revealed that increased dietary metal intake reduced the odds ratio of ED. 1:1 PSM reanalysis further confirmed the validity of the results. Conclusion: Increasing dietary intake of trace metals (magnesium, zinc, copper, selenium) within the upper limit is beneficial in reducing the prevalence of ED. Keywords: Dietary trace metals intake; Erectile dysfunction; Nutrition; Atherosclerosis.